FEATURES OF AN ESTIMATION OF INVESTMENT PROJECTS AT THE ENTERPRISES OF AVIATION INSTRUMENT - Petr P. Dobrov (Модернизация, инновация, развитие, 2016)
The relevance of this study due to the fact that the current situation in Russia is complemented by the negative effects of market reforms in the economy and economic sanctions adopted against our country and in particular the different level companies. In view of this, to effectively manage the activities and the development of aviation instrument companies and enterprises of different ownership forms are highly relevant issues related to the assessment of investment projects. The general crisis that engulfed almost all industry in Russia, demanded the application of a new ideology of the organization and management of investment projects, as well as their assessment at the enterprises of aviation instrument. In Russia, began a new stage in the development of project management establishment of a domestic methodology, complex tools and training for professional project management on the basis of domestic achievements, global experience and creativity of its processing based on the actual conditions of our country. The need for the use of project management methodology in Russia is determined by two factors: the increasing complexity of projects and the organizations that operate them, and the fact that project management is widely used in countries with market economies. Projects at the enterprises of aviation instrument making and evaluation are characterized by complexity and uncertainty, a significant dependence on the dynamic environment, including socio-economic, political, financial, economic, legislative influence of both the state and competing companies. In this paper, a study of modern methods of evaluating investment projects at the enterprises of aviation instrument. Methodology. The methodological basis of this paper appeared comparative and economic-mathematical analysis methods. Results. As part of the presentation of the present article the author, it was found that the activity of modern companies is not linear and is determined by a variety of environmental factors that can influence the reliability and stability of business development of the company. In the new (innovative or cognitive), the economy is not only a change of theoretical and empirical management paradigms based on a new understanding of the interaction of three key institutional actors (government, business and science), but also increases the level of uncertainty in making long-term management decisions related to investment projects. Conclusions / relevance. The proposed structure of the investment decision-making support system shows that a lot of administrative decisions should be localized in phase space is defined as a business reliability of the border. Output solutions beyond the phase space of growth and potentiates the risk may mean the loss of stability of the company. The bulk of the toolkit developed procedures formalized and rigorously justified, which greatly reduces the proportion of subjectivity inherent in all existing methods of management analysis.